Measurement of trilinear gauge boson couplings from WW plus WZ -> lvjj events in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Blazey, G.; et al. (Amer Physical Soc, 2009)
We present a direct measurement of trilinear gauge boson couplings at gamma WW and ZWW vertices inWW and WZ events produced in p (p) over bar collisions at root s = 1:96 TeV. We consider events with one electron or muon, missing transverse energy, and at least two jets. The data were collected using the D0 detector and correspond to 1:1 fb(-1) of integrated luminosity. Considering two different relations between the couplings at the gamma WW and ZWW vertices, we measure these couplings at 68% C.L. to be kappa(gamma) = 1.07(-0.29)(+0.26) lambda = 0.00(-0.06)(+0.00), and g(1)(Z) = 1.04(-0.09)(+0.09) in a scenario respecting SU(2)(L) circle times U(1)(Y) gauge symmetry and kappa = 1.04(-0.11)(+0.11) and lambda = 0.00(-0.06)(+0.06) in an equal couplings'' scenario.